ANALISIS PENDAPATAN PETANI BUAH NAGA Di DESA SAMBIREJO KECAMATAN BANGOREJO KABUPATEN BANYUWANGI - Andri Setiawan; Aris Soelistiyo (Jurnal Ilmu Ekonomi JIE, 2017)
This study aims at finding the income rate, the Break Event Point (BEP) and the efficiencly of dragon fruit farmers at Sambirejo village of Bangorejo sub district of Banyuwangi regency. The analytical tool used in this study was the quantitative descriptive toward the level of income, Break Event Point (BEP) and efficiency. The result of the study showed that : 1) The nett income of dragon fruit farmers at Sambirejo village is Rp. 5.648.815.000 with its average income of Rp. 282.440.750; 2) The Break Event Point of dragon fruit farmer at Sambirejo village is 14.353 Kg, therefore it can be concluded that this business is worth to process for its production value is bigger than its BEP; 3) The R/C efficiency rate of dragon fruit farmer at Sambirejo village is 3.32>1 which means the farmers are in good condition or is gaining profit and they have good prospect in its improvement for the R/C value > 1, that is 3.32Keywords: Income, Break Event Point (BEP) and Efficiency